2022
DOI: 10.3389/fpls.2022.1072394
|View full text |Cite
|
Sign up to set email alerts
|

‘Priming’ protects Piper nigrum L. from Phytophthora capsici through reinforcement of phenylpropanoid pathway and possible enhancement of Piperine biosynthesis

Abstract: Piper nigrum L. (black pepper), a woody perennial spice crop indigenous to India is positioned at the phylogenetically unique basal lineage of angiosperms. Cultivation of this major spice crop is constrained by rampant fungal and viral infections leading to a lack of disease-free planting material. The major disease that poses severe threat to P. nigrum plantations and nurseries is ‘quick wilt’ caused by the oomycete Phytophthora capsici, which affects the leaf, stem, spike, collar and root. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…This protein has been observed to induce necrotic responses in the host plant Nicotiana benthamiana 25 . Previous research from our lab has shown that P. capsici initiates hyphal growth in P. nigrum within 6 hpi and proliferates extensively on the leaf, resulting in the formation of progressing necrotic lesions within 24 hpi 40 . Our analysis of NPP1 gene expression in this study aligns with these findings, revealing a peak expression between 12 and 24 hpi, followed by a decrease by 48 hpi.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This protein has been observed to induce necrotic responses in the host plant Nicotiana benthamiana 25 . Previous research from our lab has shown that P. capsici initiates hyphal growth in P. nigrum within 6 hpi and proliferates extensively on the leaf, resulting in the formation of progressing necrotic lesions within 24 hpi 40 . Our analysis of NPP1 gene expression in this study aligns with these findings, revealing a peak expression between 12 and 24 hpi, followed by a decrease by 48 hpi.…”
Section: Discussionmentioning
confidence: 85%
“…However, there is a noticeable scarcity of studies focusing on this aspect, particularly in the field of crop plants 37 and phytopathogens 38 . Piper nigrum , commonly known as black pepper is an important non-model spice crop that is susceptible to a highly destructive disease called quick-wilt or foot rot caused by the pathogen, Phytophthora capsici 39 , 40 . The suitability of different RGs in conducting expression studies in the host plant ( P. nigrum ) in response to P. capsici infection has been reported earlier 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Crop loss due to pathogens represents a major challenge for the black pepper industry. Two common pathogens severely affecting black pepper cultivation are Phytophthora capsici and Meloidogyne incognita (Indu et al, 2022; Mahadevan et al, 2016; Tran et al, 2019; Truong et al, 2010; Verma et al, 2023). In addition, it is well known that black pepper plants require well‐drained soil (Nair, 2011; Sadanandan, 2000), which means that black pepper cultivation is hampered in parts of Asia where frequent rainfall and flooding are common.…”
Section: Introductionmentioning
confidence: 99%